Ech ixe’t u ch’aao: Land, Gender, and Kinship in the Roots of the War in San Juan Cotzal, Guatemala - Palencia Frener, Sergio Guillermo (2025)
This essay studies the violence at “the beginning of the war” (ixe’t u ch’aao) in San Juan Cotzal, a municipality located in northwest Guatemala. To this end, it analyzes oral histories, testimonies, and memories of two Ixil cousins that suffered the kidnapping of their fathers Domingo Sajic and Francisco Córdova at an early age in 1969-1973. Both recount the accusations, persecution, and the consequences of violence on women and children in the home. From a gender perspective, this work follows the levels of conflict, temporalities, sequences, and emotions in these indigenous accounts. The cousins’ account clarify and go beyond the male emphasis in Mario Payeras’ take of Sajic’s death, as well as the war historiography centered on male politicians in the public sphere. Considering the experience at home, the politics of their actions and genderized memory, these two female memories emphasize the dynamics of ch’exel and Ixil kinship. Finally, this essay brings forth the importance of envy (chi’nank’u’lil) as a central element in the origin of the war in the Maya highlands.